Optical emission from Eu, Tb, Nd luminescence centers in TiO2 prepared by magnetron sputtering - Kaczmarek, Danuta; Domaradzki, Jarosław; Borkowska, Agnieszka; Podhorodecki, Artur; Misiewicz, Jan; Sieradzka, Karolina (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
This work presents the results of optical emission from Eu3+, Tb3+ and Nd3+ luminescence centers in TiO2 thin films. Thin films were prepared by magnetron sputtering from metallic Ti-Eu, Ti-Tb, Ti-Nd targets, respectively. Optical properties were examined by means of photoluminescence and optical transmission measurements. The total content of dopants was analyzed using an energy disperse spectrometer. It has been shown that doping of TiO2 thin films using selected lanthanides results in the visible (Eu, Tb) and near-infrared (Nd) light emission, upon ultraviolet radiation. Additionally, transparency range and optical band gap of prepared thin films were determined, in comparison to pure TiO2.
Optica Applicata, Vol. 37, 2007, nr 4, s. 433-438
Keywords: optyka; luminescence; rare earth elements; TiO2; magnetron sputtering